The Role of Magnetic Quantum Dot Cellular Automata In Replacing Traditional CMOS Technology - Umamahesvari, H (International Journal of Computer Sciences and Engineering, 2025)
The uprising innovation of nanotechnology is Quantum dot cellular automata (QCA). Quantum Dot Cellular Automata is a new paradigm “Molecules can act as switches“. QCA is fulfilling the gap left by the conventional memory systems in consuming power. There are various types of QCAs reported till now like Metal dot QCA, Molecular QCA and Magnetic QCA, metal Dot QCA has its own limitation that it can be operated only at low temperature. Though molecular QCA s are proved to be superior in operating condition compare to Metal- Dot QCA which can be operated at room temperature it also meets its own downside that its fabrication becomes complicated. In general most of the quantum dots include hundreds or thousands of atoms with variation in their energy and wave function. So creating quantum dots with digital reliability by eliminating the variations size, shape and arrangement remains indefinable. Since we need to go for a alternative device indeed to avoid the maximum power dissipation met with the high density ICs, let us think about the Magnetic QCA. Magnetic QCA relay on the property of alignment of spins in ferromagnetic material. The word” Quantum” implies quantum mechanical nature of short range exchange interaction which leads to alignment of spins. So Magnetic QCAs are having advantages over the previous two types that it is relatively uncomplicated. So in this paper we elaborately discuss about the QCAs, Types of QCAs and their functioning and the advantages of Magnetic QCA